The Gods among Us: A Shared Recipe for Making Saints in Early Jewish and Daoist Hagiographies - Shen, Jianyu (Religions, 2024)
This article examines the earthly journey of the saints in early Jewish and Daoist hagiographies. The major texts for comparative reading are Sefer Shivchei Ha-Ar”i and Shenxian Zhuan, namely, the foundation stones of each hagiographical tradition. Emphasis is laid on the most significant phases in the process of making saints while the candidates dwell in the worldly domain as quasi-divine beings: (1) Mystical Birth, (2) Life in Seclusion, and (3) Divine Encounters. During these stages of transition, the sages were imparted with the esoteric wisdom and the godly features that rendered them extraordinary exemplars of religiosity. My investigation demonstrates that this recipe is shared by both hagiographical traditions, despite the distance in time and space, to construct the image of saints, each expressed with culturally distinct characteristics of their own. I argue that both traditions display a pattern of human-centered sainthood instead of the divine-endorsed type—while the birth myth shows a discernible degree of predestined sagehood, painstaking periods, such as self-isolation and learning with the true masters, are more crucial to the sages’ transformation of identity in the realm of Earth, the dynamic incubator that breeds holiness for the most qualified souls.